Monitoring of immune activation using biochemical changes in a porcine model of cardiac arrest - Anton Amann; Bernhard Widner; Josef Rieder; Herwig Antretter; Georg Hoffmann; Viktoria Mayr; Hans-Ulrich Strohmenger; Dietmar Fuchs (Mediators of Inflammation)
In animal models, immune activation is often difficult to assess because of the limited availability of specific assays to detect cytokine activities. In human monocytes/macrophages, interferon-γ induces increased production of neopterin and an enhanced activity of indoleamine 2,3-dioxygenase, which degrades tryptophan via the kynurenine pathway. Therefore, monitoring of neopterin concentrations and of tryptophan degradation can serve to detect the extent of T helper cell 1-type immune activation during cellular immune response in humans. In a porcine model of cardiac arrest, we examined the potential use of neopterin measurements and determination of the tryptophan degradation rate as a means of estimating the extent of immune activation. Urinary neopterin concentrations were measured with high-performance liquid chromatography (HPLC) and radioimmunoassay (RIA) (BRAHMS Diagnostica, Berlin, Germany). Serum and plasma tryptophan and kynurenine concentrations were also determined using HPLC. Serum and urine neopterin concentrations were not detectable with HPLC in these specimens, whereas RIA gave weakly (presumably false) positive results. The mean serum tryptophan concentration was 39.0 Ī 6.2 μmol/l, and the mean kynurenine concentration was 0.85 Ī 0.33 μmol/l. The average kynurenine-per-tryptophan quotient in serum was 21.7Ī 8.4 nmol/μmol, and that in plasma was 20.7Ī 9.5 nmol/μmol (n = 7), which corresponds well to normal values in humans. This study provides preliminary data to support the monitoring of tryptophan degradation but not neopterin concentrations as a potential means of detecting immune activation in a porcine model. The kynurenine-per-tryptophan quotient may serve as a short-term measurement of immune activation and hence permit an estimate of the extent of immune activation.